Zagadnienie bezpośredniości dostępu poznawczego do własnych stanów mentalnych - Pacholik-Żuromska, Anita (Filozofia Nauki, 2010)
The question of subject's cognitive access to his own mental states contains an assumption, that this cognition is direct and authoritative, what is also a condition of subject's self-knowledge. The directness means, that this kind of cognition is not burdened by the intermediaries as Fregean senses or representations. Now arises the problem, how the self-knowledge, which has a propositional character can be direct, hence nonrepresentational. In this paper I considered the three kinds of representations, which are present in self-knowledge and I have tried to answer the question, whether it is possible to preserve the directness of self-knowledge, despite of its representational constituents. First I have asked about the representation of self, then I assumed that to have self-knowledge a subject has to conceptualise his state as a belief or other experience of a certain kind and he has to think about himself as a subject of this state. Then I considered the representation of the modality of the state. Finally I analysed the representational character of the content of mental states. The conclusion of these investigations was that even if the self-knowledge in its epistemological aspect is representational (for example because of its propositional structure) it preserves its directness in its essential form, i.e. psychological aspect.